Optically active polyaromatic Schiff base adopting stable secondary structures. (22nd February 2023) - Tada, Kazuki; Ikegaki, Chiaki; Fuse, Yuki; Tateishi, Kazuki; Sogawa, Hiromitsu; Sanda, Fumio
Abstract: The polycondensation of N -((3, 5-diamino)benzoyl)-ʟ-alanine dodecyl ester (1L ) with p -phthalaldehyde (2 ) was carried out to obtain poly(1L -2 ), a novel optically active polymer containing Schiff base moieties in the main chain. A series of analogous polymers with Schiff base moieties were also synthesized from N -((3, 5-diamino)benzoyl)-ᴅ-alanine dodecyl ester (1D ) and N -((3, 5-diamino)benzoyl)glycine dodecyl ester (1G ) with various feed ratios. The polymers exhibited CD signals assignable to exciton coupling-based chirality in CHCl3 depending on the feed molar ratios of 1L /1D and 1L /1G . Poly(1L -2 ) exhibited lyotropic liquid crystallinity in CHCl3 and THF. Graphical abstract: Image 1 Highlights: Optically active Schiff base polymers are synthesized. The polymers exhibit CD signals assignable to exciton coupling-based chirality. Molecular dynamics simulations properly predict the folded helical conformation. The polymers exhibit lyotropic liquid crystallinity.